Smart and innovative trends in next generation computing technologies. third International Conference, NGCT 2017, Dehradun, India, October 30-31, 2017, Revised selected papers /: third International Conference, NGCT 2017, Dehradun, India, October 30-31, 2017, Revised selected papers. Part II : (2018) - Unknown
No abstract available